Artisanat et savoir-faire : archéologie des techniques - Bouché, Fanny; Bouzaglou, Liora; Pinto, Alexandre; Sauvageot, Prune (Archéo.doct, 2020)
From the smallest fragments to megalithic constructions, and through ceramic, metal or bone, the study of artefacts and ecofacts has greatly developed since the beginnings of archaeology by proposing innovative methods focused on the reconstruction of material and/or immaterial knowledge and know-how, technical gestures and the history of craftsmen and their production. It is precisely in this perspective that the 14th doctoral day is being held. The papers presented during this day, gathered in the present volume, focused on the restitution of different "chaînes opératoires", rather complete or focused on one specific aspect, as well as on the methods and methodologies developed to access them, such as experimental, ethnoarchaeological or technological approaches. The richness of this theme rests, inter alia, on the diversity of the topics covered, from metallurgy to agricultural techniques, and from construction techniques to everyday objects.